Bioprinting of Decellularized Porcine Cardiac Tissue for Large-Scale Aortic Models - Oropeza, Beu P.; Adams, Jason R.; Furth, Michael E.; Chessa, Jack; Boland, Thomas (Frontiers in Bioengineering and Biotechnology, 2022)
Bioprinting is an emerging technique used to layer extrudable materials and cells into simple constructs to engineer tissue or arrive at in vitro organ models. Although many examples of bioprinted tissues exist, many lack the biochemical complexity found in the native extracellular matrix. Therefore, the resulting tissues may be less competent than native tissues—this can be especially problematic for tissues that need strong mechanical properties, such as cardiac or those found in the great vessels. Decellularization of native tissues combined with processing for bioprinting may improve the cellular environment for proliferation, biochemical signaling, and improved mechanical characteristics for better outcomes. Whole porcine hearts were decellularized using a series of detergents, followed by lyophilization and mechanical grinding in order to produce a fine powder. Temperature-controlled enzymatic digestion was done to allow for the resuspension of the decellularized extracellular matrix into a pre-gel solution. Using a commercial extrusion bioprinter with a temperature-controlled printhead, a 1:1 scale model of a human ascending aorta and dog bone shaped structures were printed into a reservoir of alginate and xanthium gum then allowed to crosslink at 37C. The bioengineered aortic construct was monitored for cell adhesion, survival, and proliferation through fluorescent microscopy. The dog bone structure was subjected to tensile mechanical testing in order to determine structural and mechanical patterns for comparison to native tissue structures. The stability of the engineered structure was maintained throughout the printing process, allowing for a final structure that upheld the dimensions of the original Computer-Aided Design model. The decellularized ECM (Ē = 920 kPa) exhibited almost three times greater elasticity than the porcine cardiac tissue (Ē = 330 kPa). Similarly, the porcine cardiac tissue displayed two times the deformation than that of the printed decellularized ECM. Cell proliferation and attachment were observed during the in vitro cell survivability assessment of human aortic smooth muscle cells within the extracellular matrix, along with no morphological abnormalities to the cell structure. These observations allow us to report the ability to bioprint mechanically stable, cell-laden structures that serve as a bridge in the current knowledge gap, which could lead to future work involving complex, large-scale tissue models.